How transformative innovations shaped the rise of nations : from ancient Rome to modern America - Tellis, Gerard J., 1950-; Rosenzweig, Stav (Anthem Press, an imprint of Wimbledon Publishing Company, 2018)
Over the last 2,000 years, critical innovations have transformed small regions into global powers. But these powers have faded when they did not embrace the next big innovation. Gerard J. Tellis and Stav Rosenzweig argue that openness to new ideas and people, empowerment of individuals and competition are key drivers in the development and adoption of transformative innovations. These innovations, in turn, fuel economic growth, national dominance and global leadership. In How Transformative Innovations Shaped the Rise of Nations, Tellis and Rosenzweig examine the transformative qualities of concrete in Rome; swift equine warfare in Mongolia; critical navigational innovations in the golden ages of Chinese, Venetian, Portuguese and Dutch empires; the patent system and steam engine in Britain; and mass production in the United States of America.